Clinical supervision strategies, learning, and critical thinking of nursing students - Angélica Oliveira Veríssimo da Silva; António Luís Rodrigues Faria de Carvalho; Rui Marques Vieira; Cristina Maria Correia Barroso Pinto (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objective: To identify the supervisory strategies that Nursing students consider facilitators of the development of critical thinking skills in clinical teaching. Methods: This is a qualitative study, within the interpretative paradigm, using the focus group methodology. Eight undergraduate nursing students participated in the study. Results: Participants recognized the indispensability of critical thinking for professional responsibility and quality of care and highlighted the importance of using supervisory strategies adapted to their needs, learning objectives, and the context of clinical practice. Final considerations: This study highlights the urgent need to establish, within the Nursing curricula, clinical supervision strategies that promote critical thinking and favor the development of skills for good clinical judgment, problem solving, and safe, effective, and ethical decision-making.